Use of YouTube as a Source of Information for Quitting or Cutting Down Alcohol - Al Mahmud, Abdullah; Le, Anh; Mubin, Omar (Frontiers in Public Health, 2021)
Background: Although research has been done on considering YouTube for dissuading and encouraging unhealthy behaviours such as smoking, less focus has been placed on its role in quitting or cutting down alcohol. This study aims to analyse the alcohol cessation videos available and accessible on YouTube to gain a more in-depth insight into the ways that YouTube as a platform is being used to persuade with relation to alcohol cessation. Methods: We systematically searched for content on YouTube related to alcohol cessation and these videos were analysed and evaluated for the format, themes, specific alcohol cessation advice, and uploader. Results: The results demonstrated that the collected alcohol cessation videos included a fairly even presence of the themes of discussing the negative impacts of alcohol and the benefits of quitting or staying away from it. At the same time, however, we found the videos were not sourced from professional institutions, such as government or anti-alcohol misuse non-government organisations. Conclusion: More research is needed to investigate utilising YouTube to support those looking to quit or cut down alcohol.